Essays in applied econometrics - Duarte, Rafael Burjack Farias (2015)
Using a unique dataset on Brazilian nominal and real yield curves combined with daily survey forecasts of macroeconomic variables such as GDP growth, inflation, and exchange rate movements, we identify the effect of surprises to the Brazilian interbank target rate on expected future nominal and real short rates, term premia, and inflation expectations. We find that positive surprises to target rates lead to higher expected nominal and real interest rates and reduced nominal and inflation term premia. We also find a strongly positive relation between both real and nominal term premia and measures of dispersion in survey forecasts. Uncertainty about future exchange rates is a particularly important driver of variations in Brazilian term premia.